The Clamping of End-Tidal Carbon Dioxide Does Not Influence Cognitive Function Performance During Moderate Hyperthermia With or Without Skin Temperature Manipulation - Schultz Martins, Ricardo; Wallace, Phillip J.; Steele, Scott W.; Scott, Jake S.; Taber, Michael J.; Hartley, Geoffrey L.; Cheung, Stephen S. (Frontiers in Psychology, 2021)
Increases in body temperature from heat stress (i.e. hyperthermia) generally impairs cognitive function across a range of domains and complexities, but the relative contribution from skin versus core temperature changes remains unclear. Hyperthermia also elicits a hyperventilatory response that decreases the partial pressure of end-tidal carbon dioxide (PetCO2) and subsequently middle cerebral artery velocity (MCAv) that may influence cognitive function. We studied the role of skin and core temperature along with PetCO2 on cognitive function across a range of domains. Eleven males completed a randomized, single-blinded protocol consisting of poikilocapnia (POIKI, no PetCO2 control) or isocapnia (ISO, PetCO2 maintained at baseline levels) during passive heating using a water-perfused suit (water temperature ~49°C) while MCAv was measured continuously using transcranial Doppler. Cognitive testing was completed at baseline, neutral core-hot skin (37.0 ± 0.2˚C-37.4 ± 0.3˚C), hot core-hot skin (38.6±0.3˚C-38.7±0.2˚C), and hot core-cooled skin (38.5 ± 0.3˚C-34.7 ± 0.6˚C). The cognitive test battery consisted of a detection task (psychomotor processing), 2-back task (working memory), set-shifting and Groton Maze Learning Task (executive function). At hot core-hot skin, poikilocapnia led to significant (both p < 0.05) decreases in PetCO2 (∆-21%) and MCAv (∆-26%) from baseline, while isocapnia clamped PetCO2 (∆+4% from baseline) leading to a significantly (p=0.023) higher MCAv (∆-18% from baseline) compared to poikilocapnia. There were no significant differences in errors made on any task (all p > 0.05) irrespective of skin temperature or PetCO2 manipulation. We conclude that neither skin temperature nor PetCO2 maintenance significantly alter cognitive function during passive hyperthermia.